Uncle Sam in Pinstripes : Evaluating U.S. Federal Credit Programs - Elliott, Douglas J., 1959- (Book collections on Project MUSE., 2011)
It is a long-held perception that America is a nation where the government typically stays out of day-to-day business activities. Yet the U.S. federal government is in many ways the biggest and most influential financial institution in the world, with 10 trillion in federal guarantees and loans going to the private sector. Even before recent implementation of massive interventions meant to stave off financial calamity, the federal government directly or indirectly provided significantly more credit than any of the country's largest private sector banks. And, of course, the government's credit.